2008
DOI: 10.3201/eid1407.070894
|View full text |Cite
|
Sign up to set email alerts
|

Alcaligenes xylosoxidansBloodstream Infections in Outpatient Oncology Office

Abstract: In 2002, we investigated a cluster of patients with Alcaligenes xylosoxidans bloodstream infections by conducting a matched case-control study and a prospective study. Pulsed-fi eld gel electrophoresis (PFGE) was performed on blood culture isolates, and 1 explanted central venous catheter (CVC) was tested for biofi lm. We identifi ed 12 cases of A. xylosoxidans bloodstream infection. Case-patients were more likely than controls to have had a CVC (7/7 [100%] vs 4/47 [8.7%], respectively; p<0.0001). Ten case iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…, Gristina & Costerton (1985), Marrie & Costerton (1985) Endocarditis Stewart et al (1980) Device-related bacteremia is thought to be due primarily to erosion or sloughing of biofilm cells because of mechanical shear when flushing the catheter, which detaches microbial cells from a biofilm (Donlan, 2002) and results in cells or cell aggregates entering the bloodstream and leading to the signs and symptoms of blood stream infection. Indwelling catheters are frequently colonized with biofilm shortly after insertion (Donlan & Costerton, 2002), and Kim et al linked biofilm on a central venous catheter (CVC) to an outbreak of Alcaligenes xylosoxidans bloodstream infection (Kim et al, 2008b). Many others, including Raad et al, 1992, Yücel et al, 2004, Lorente et al, 2004, have noted that catheter colonization does not necessarily directly correlate with infection as measured by positive blood cultures.…”
Section: Criteria For Baimentioning
confidence: 99%
See 1 more Smart Citation
“…, Gristina & Costerton (1985), Marrie & Costerton (1985) Endocarditis Stewart et al (1980) Device-related bacteremia is thought to be due primarily to erosion or sloughing of biofilm cells because of mechanical shear when flushing the catheter, which detaches microbial cells from a biofilm (Donlan, 2002) and results in cells or cell aggregates entering the bloodstream and leading to the signs and symptoms of blood stream infection. Indwelling catheters are frequently colonized with biofilm shortly after insertion (Donlan & Costerton, 2002), and Kim et al linked biofilm on a central venous catheter (CVC) to an outbreak of Alcaligenes xylosoxidans bloodstream infection (Kim et al, 2008b). Many others, including Raad et al, 1992, Yücel et al, 2004, Lorente et al, 2004, have noted that catheter colonization does not necessarily directly correlate with infection as measured by positive blood cultures.…”
Section: Criteria For Baimentioning
confidence: 99%
“…Indwelling catheters are frequently colonized with biofilm shortly after insertion (Donlan & Costerton, ), and Kim et al . linked biofilm on a central venous catheter (CVC) to an outbreak of Alcaligenes xylosoxidans bloodstream infection (Kim et al ., ). Many others, including Raad et al ., , , Yücel et al ., , Lorente et al ., , have noted that catheter colonization does not necessarily directly correlate with infection as measured by positive blood cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that Achromobacter spp. can form biofilm on surfaces other than CL, such as central venous catheters and urinary catheters [15,16]. The presence of biofilms in sputum from cystic fibrosis (CF) patients infected with A. xylosoxidans was revealed in one study.…”
Section: Discussionmentioning
confidence: 99%
“…xylosoxidans, also known as Achromobacter xylosoxidans, is a gram-negative aerobic organism with close relationship to pseudomonas [5] . This organism has been reported in immunosuppressed patients such as those with cystic fibrosis or indwelling hardware [3] . A. xylosoxidans peritonitis has a poor prognosis because of pathogen's virulence and a high rate of recurrence [1] .…”
Section: Discussionmentioning
confidence: 99%